Analisis Nilai-nilai Pendidikan Moral dalam 21 Cerita Rakyat Bumi Lancang Kuning Susunan Yeni Maulina dan Crisna Putri Kurniati - Safira, Dina; Erni, Erni (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
Educational values ​​are concepts and ideals that are important and useful for humans. In its division, the value of education also includes morals, namely the view of the values ​​of truth and one's ability to distinguish between good and bad. One of the literary works that contains the value of moral education in it is folklore. The problems studied in this study are (1) how is the value of moral responsibility contained in 21 Folk Stories of Bumi Lancang Kuning composed by Yeni Maulina and Crisna Putri Kurniati? (2) what is the value of human conscience contained in 21 Folk Stories of Bumi Lancang Kuning by Yeni Maulina and Crisna Putri Kurniati? (3) what is the value of the rights and obligations contained in 21 Folk Stories of Bumi Lancang Kuning composed by Yeni Maulina and Crisna Putri Kurniati? This study aims to describe and analyze data about the value of moral education including the value of moral responsibility, the value of human conscience, and the value of rights and obligations contained in 21 Folk Stories of Bumi Lancang Kuning composed by Yeni Maulina and Crisna Putri Kurniati. The theory used in this study is the theory of Ihsan (2005), Hasbullah (2005) and Salam (2000). The method used in this research is descriptive method. The data collection technique used in this research is hermeneutic. Based on data analysis on the values ​​of moral education in 21 Bumi Lancang Kuning Folklore by Yeni Maulina and Crisna Putri Kurniati, it can be concluded that (1) Of the 131 data on the value of moral education that the author found, there are 46 data on the value of human moral responsibility that consisting of 24 data on the value of consciousness, 11 data on the value of love/liking, and 11 data on the value of courage, (2) Of the 131 data on the value of moral education that the author found, there are 10 data on the value of human conscience which consists of 2 data values ​​of true and false quality. 8 data on the value of certain quality, doubtful, approximate, and confused, and (3) From 131 data on the value of moral education that the author found, there are 75 data on the value of human rights and obligations consisting of 8 data on the value of human obligations to God, 13 data on moral values ​​in family life, 13 data on moral values ​​of parents to children, 20 data on moral values ​​of children to parents, 4 data on moral values ​​in neighborly life, 1 dat a moral values ​​of students in learning, and 16 data on morals in leadership.